Gene Expression Profiling of Alcoholic Liver Disease in the Baboon (Papio hamadryas) and Human Liver - Seth, Devanshi (American Society for Investigative Pathology, 2003)
The molecular pathogenesis of alcoholic liver disease (ALD) is not well understood. Gene expression profiling has the potential to identify new pathways and altered molecules in ALD. Gene expression profiles of ALD in a baboon model and humans were compared using DNA arrays. Reverse transcriptase-polymerase chain reaction and immunohistochemistry were used for downstream analysis of array results. cDNA array analysis revealed differential expression of several novel genes and pathways in addition to genes known to be involved in ALD pathogenesis. Overall gene expression profiles were similar in both species, with a majority of genes involved with fibrogenesis and xenobiotic metabolism, as well as inflammation, oxidant stress, and cell signaling. Genes associated with stellate cell activation (collagens, matrix metalloproteinases, tissue inhibitors of matrix metalloproteinase) were up-regulated in humans. Decreased expression of several metallothioneins was unexpected. Fourteen molecules related to the annexin family were up-regulated, including annexin A1 and A2. Immunofluorescence revealed a marked overexpression of annexin A2 in proliferating bile duct cells, hepatocyte cell surface, and selective co-localization with CD14-positive cells in human ALD. The gene expression profile of ALD is dominated by alcohol metabolism and inflammation and differs from other liver diseases. Annexins may play a role in the progression of fibrosis in ALD.